2021
DOI: 10.1073/pnas.2008778118
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging reveals compartmentalization of mitochondrial protein synthesis in cultured human cells

Abstract: Human mitochondria contain their own genome, mitochondrial DNA, that is expressed in the mitochondrial matrix. This genome encodes 13 vital polypeptides that are components of the multisubunit complexes that couple oxidative phosphorylation (OXPHOS). The inner mitochondrial membrane that houses these complexes comprises the inner boundary membrane that runs parallel to the outer membrane, infoldings that form the cristae membranes, and the cristae junctions that separate the two. It is in these cristae membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 49 publications
(66 reference statements)
4
43
0
Order By: Relevance
“…The focus of this mini-series is mitochondrial heterogeneity. Our data presented here and that of another recent publication [19] show clearly that for at least certain human cell lines there is evidence of marked heterogeneity in the location of translation within the mitochondrial network. Normalising mitochondrial signal using markers to either the outer mitochondrial membrane (TOM20) or the cristae membranes (FoF1 ATP synthase) confirm new protein synthesis is more markedly concentrated within the perinuclear mitochondrial network rather than towards the cell periphery.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The focus of this mini-series is mitochondrial heterogeneity. Our data presented here and that of another recent publication [19] show clearly that for at least certain human cell lines there is evidence of marked heterogeneity in the location of translation within the mitochondrial network. Normalising mitochondrial signal using markers to either the outer mitochondrial membrane (TOM20) or the cristae membranes (FoF1 ATP synthase) confirm new protein synthesis is more markedly concentrated within the perinuclear mitochondrial network rather than towards the cell periphery.…”
Section: Discussionsupporting
confidence: 77%
“…By exploiting the technique of click chemistry in a process termed mitochondrial FUNCAT (Fluorescent Noncanocial Aminoacid Tagging), our laboratory was able to show that newly synthesised proteins were mostly located at the cristal membranes [19]. We now report that further use of mitochondrial FUNCAT reveals a heterogeneous distribution of translation within the mitochondrial network in cultured cells, with a far greater level of synthesis occurring in the perinuclear region of the network as compared to the periphery after normalisation to mitochondrial mass.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Until now, the precise identity of the transcripts present in the MRGs has not been revealed, and it would be interesting to know whether polycistronic, immature transcripts occupy the same or a different location as the mature transcripts ready for translation. A recent study by Zorkau et al [17] has suggested that the mitoribosomes could be loaded with mature transcripts that are close to MRGs but not within them. The authors measured the spatiotemporal kinetics of mitochondrial protein synthesis by using fluorescent noncanonical amino acid tagging.…”
Section: Rna Composition Of Mrgsmentioning
confidence: 99%